Study on Development of Virgin Coconut Oil Agroindustry System in North Sulawesi, Indonesia - Herry Frits Pinatik; I Ketut Satriawan; Dwi Putra Darmawan; I Wayan Widia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The development of virgin coconut oil (VCO) agro-industry products has been studied. Research objectives are; 1). Analyzing the added value of VCO processing agroindustry on the scale of UMKM in North Sulawesi Province 2). Determining the factors that influence the added value. This study uses the Hayami value added analysis method. The results of the study found that for every use of 1 kg of raw coconut meat processed into VCO products, UMKM business actors received a profit of Rp. 19.771.71, meaning that from agricultural activities in processing VCO products, UMKM actors get a significant economic value added. The conclusions of this study are: 1). Analysis of the added value of the Virgin Coconut Oil (VCO) agroindustry in North Sulawesi, the output value is Rp. 31,428.57/liter, the added value generated is Rp. 21,428.57, - with a ratio of 68.18%, labor compensation work amounting to Rp 1,656.86/liter or 7.73%, and a profit margin of Rp 21,428.57/liter or 92.27%; 2). The factors that influence the added value are raw materials, product prices, labor coefficient, conversion factors and the average wage of labor.